Design Of Wideband RF Front End Wireless Transceiver - Zubir, Ihsan Ahmad (2012)
In this thesis, a wireless transceiver operating at 5.8 GHz for image transmission application is designed and fabricated. It provides wide bandwidth of 200 MHz with noise figure of 2.5 dB. The transceiver‟s prototype was built using off-the-shelf components from Mini-Circuit and Hittite except 132 MHz and 5.8 GHz bandpass filter. It consists of a superheterodyne receiver and a superheterodyne transmitter analog front-end together with local oscillator and IF amplifier. Superheterodyne architecture was implemented in this transceiver design because it is not complicated design and suitable for high resolution ADCs operating over 320MHz.